Extraction, purification, structural features, biological activities, and applications of polysaccharides from Opuntia ficus-indica (L.) Mill. (cactus): a review - Liu, Xudong; Xing, Yan; Liu, Guijun; Bao, Dapeng; Hu, Wenjing; Bi, Haizheng; Wang, Meng (Frontiers in Pharmacology, 2025)
Cactus has attracted increasing attention from researchers due to its rich nutritional, edible, and medicinal value. Cactus contains abundant polysaccharides, polyphenols, vitamins, amino acids, minerals, and more. Among them, polysaccharides are considered as important bioactive components in cactus. In the past period, polysaccharides have been isolated from cactus through various methods and their structures have also been studied. Some in vivo and in vitro experimental results indicate that cactus polysaccharides have promoting wound healing, anti-inflammatory, immune regulation, anti-glycosylation, and antioxidant effects. This article reviews the research progress in the extraction, purification, structural characteristics, and biological activities of cactus polysaccharides in recent years. In addition, the relationship between the structure and activity of cactus polysaccharides was also discussed. This review provides important research basis and latest information for the in-depth development and application of cactus polysaccharides in multiple fields such as medicine and functional foods.